Translation of Weiman Kou’s ‘Corona Virus’ Comic into Indonesian: Covid-19 Prevention Educational Strategy - Mirsa Umiyati; I Gusti Ayu Agung Dian Susanthi; Daimond Tavares Rosa Suhartono (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
The Covid-19 pandemic having been spreading throughout the world has resulted in the emergence of various literary works with the aim of educating the wider community on how to anticipate it. One form of literary work helping educate and is well responded to by the community, especially school-aged children, is comics. Comics are very effective in attracting people to listen and read since the information is conveyed in attractive pictures and in easily digestible language. The comics written are translated into various languages ​​so that people in the regions and speakers of other languages ​​can receive the messages conveyed through the comics in question. Identifying the advantages of comics in educating the prevention of Covid-19 around the world, this research focuses on examining the process of translating a comic by Weiman Kou into Balinese. Translation is an effective way to develop learning, not only in college but also in the wider community environment. This study examines the procedure for translating comics by graduate students of linguistics. The results showed that the comic was translated by literal, calque, and borrowing procedures. In order to achieve quality translation results, it is suggested that translating does not only apply three types of procedures but also many other types of procedures, including communicative and idiomatic procedures. By applying these procedures, the message conveyed is perceived the same to both the source language reader and the target language reader.